Translanguaging and Decolonisation in South African Higher Education: Embracing Multilingual Pedagogies - Mbirimi-Hungwe, Vimbai; Matariro-Mutanha, Mariyeni (Universitas Pendidikan Mandalika, 2024)
Translanguaging, a practice that recognises and utilizesÂ multilingual studentsâ€™ linguistic repertoires has emerged as a crucial approach in challenging traditional language policies, particularly in the South African educational landscape.Despite its embrace, a colonial stance still persists in teaching practices. Through a critical analysis of teaching materials used in an academic literacy course, this paper explores how translanguaging is currently being used in teaching and learning. Findings reveal a tension in the sense that even though studentsâ€™ language practices are acknowledged, the materials still maintain a dominant position for English. This highlights the need to move beyond a simplistic view of multilingualism towards a more holistic embrace of translanguaging.Set against this background, this research argues that translanguaging can bridge the abyssal divide created by colonialism. It emphasizes the unifying potential of translanguaging, fostering an educational landscape that celebrates South Africa's rich linguistic diversity and cultural heritage. Ultimately, the study calls upon educators to move beyond the limitations of standardized languages and fully embrace translanguaging as a transformative force for decolonization.At the end, the paper calls for further research.